The Effect of Mind Map Assistant FIPE Think Pair Share Cooperative Model on Motivation and IPS Learning Outcomes - Jamal Alam; Abdul Azis; Hidayah Quraisy (Universitas Muhammadiyah Enrekang, 2022)
The Influence of the Application of the Think Pair Share Type Cooperative Learning Model with the aid of a Mind Map on Social Studies Motivation and Learning Outcomes. Thesis. Masters Study Program for Undergraduate Basic Education (Basic Education) Faculty of Postgraduate, University of Muhammadiyah Makassar. Supervised by Abdul Azis Muslimin and Hidayah Quraisy. This study aims to determine the effect of the application of the Think Pair Share Type Cooperative Learning Model with the aid of a Mind Map on Social Studies Motivation and Learning Outcomes. This research is an experimental study using the Pretest Posttest Control Group Design which has an experimental class and a control class. The population in this study were the fifth grade students of SDN No. 62 Laikang as many as 27 people and the fifth grade students of SDN No. Of the 113 Laikang Inpres as many as 29, a total of 56 people. The data analysis technique used the Manova Test with SPSS version 21 to see the effect of the application of the Think Pair Share Type Cooperative Learning Model with the aid of a Mind Map on Students' Motivation and Social Studies Learning Outcomes. The results of this study indicate that the average value of student learning motivation for the experimental class before treatment is 62.00, the average value of learning motivation for the experimental class after treatment is 82.00. the average value of student learning motivation for the control class before treatment is 63.00, the average value of student learning motivation for the control class after treatment is 76.00. while the average value of student learning outcomes obtained in the experimental class before treatment is 66.85, the average value of student learning outcomes for the experimental class after treatment is 84.44. the average value of learning outcomes for the control class before treatment is 65.69, the average value of learning outcomes for the control class after treatment is 79.14. This proves that the application of the Think Pair Share Cooperative Learning Model with the aid of a Mind Map has an effect on the Motivation and Social Studies Learning Outcomes of Class V Students in Cluster VI, Mangarabombang District, Takalar Regency.